Decolonisation of Architectural History Education in India - Athulya Aby (University of Johannesburg, 2022)
Architectural education in India is largely envisioned as a technical-vocational course, leading to humanities-related courses like history, to remain alienated from students as well as practitioners. History of Architecture is a core subject in Bachelor of Architecture as per regulatory guidelines, but the program level outcomes are often limited to stylistic study of standard sets of examples of monumental structures from the past. This trend can be traced back to the colonial episteme started during the British programme of instruction and is ingrained in the educational system. This study enquires into the current state of history education at the undergraduate level in architectural schools in India and examines the continuing impact of colonisation on our production of knowledge. This is done by analysing the content of the architectural history curricula of colleges in India and discussions with academic practitioners who have been teaching the subject in those institutions. Unpacking the curricula and their influences on teaching, brought out the perpetuation of colonial biases embedded in architectural history education. The study argues that a well-designed history curriculum has the potential to contextualise design education and create critically aware architects, and thus take a step towards decolonising the practice itself.